Hubungan Antara Keragaman Gulma dengan Penyakit Bulai pada Jagung (Zea mays L.) Stadium Pertumbuhan Vegetatif - I MADE SUDARMA; I KETUT SUADA; KETUT AYU YULIADHI (Fakultas Pertanian Universitas Udayana, 2012)
Weeds play an important role in the spread of downy mildew disease, competition, and lower cropyields of corn. Research using the survey method in 3 locations of Sanur village, Denpasar City. Eachlocation is taken 5 samples, and each sample area was 1m2, which was arranged diagonally. Forweeds identification was using reference i.e. Weeds of rice in Indonesia, and identification of downymildew disease using reference i.e. Maize Disease: A Guide for Field Indentification and microscopically,while the weeds diversity was determined based on Diversity Index of Shannon-Wiener. Relationshipbetween number of weed species and weed populations, and disease incidence were determined byregression and correlation analysis. Weed diversity on ecosystem of maize in vegetative stage is verylow with the diversity index of 0.779, this means weed ecosystem unstable, and dominated by a particularweed species was Paspalum commersonii Lamk. (Fam. Poaceae/Graminaceae) of 23.3%, with thedominance index of 0.709. Relationship between the number of weed species and disease incidence ofthe downy mildew disease was highly significant (P<0,01), while the relationship between weed populationand disease incidence of the downy mildew disease is not significant. Plant height and leaf number ofmaize was influenced by the type of weed, but weed populations only affect plant height of maize invegetative stage (V3-V11).